Molecular basis of positional memory in limb regeneration - L. Otsuki; S. A. Plattner; Y. Taniguchi-Sugiura; F. Falcon; E. M. Tanaka (Nature, 2025)
Abstract The amputation of a salamander limb triggers anterior and posterior connective tissue cells to form distinct signalling centres that together fuel regeneration1. Anterior and posterior identities are established during development and are thought to persist for the whole life in the form of positional memory2. However, the molecular basis of positional memory and whether positional memory can be altered remain unknown. Here, we identify a positive-feedback loop that is responsible for posterior identity in the limb of an axolotl (Ambystoma mexicanum). Posterior cells express residual Hand2 transcription factor from development, and this primes them to form a Shh signalling centre after limb amputation. During regeneration, Shh signalling is also upstream of Hand2 expression. After regeneration, Shh is shut down but Hand2 is sustained, safeguarding posterior memory. We used this regeneration circuitry to convert anterior cells to a posterior-cell memory state. Transient exposure of anterior cells to Shh during regeneration kick-started an ectopic Hand2–Shh loop, leading to stable Hand2 expression and lasting competence to express Shh. Our results implicate positive-feedback in the stability of positional memory and reveal that positional memory is reprogrammed more easily in one direction (anterior to posterior) than in the other. Modifying positional memory in regenerative cells changes their signalling outputs, which has implications for tissue engineering.